2021
DOI: 10.1002/cpp.2571
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐based cognitive behavioural therapy programme with and without videoconference guidance sessions: A randomized controlled trial to treat work‐related symptoms of anxiety and depression

Abstract: This study provides the results from the implementation of a highly structured therapist‐guided iCBT programme for people with work‐related anxiety and depression, in terms of programme efficacy, participants' adherence and satisfaction. Seventy‐seven national police workers were randomly allocated to one of two groups: without additional videoconference sessions (web platform with guidance of therapist) and with additional videoconference sessions (same intervention as the previous group, plus two videoconfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…It was found that the ICBT achieved comparable scores on the improvement of cognitive therapy awareness compared with the CBT treatment. In line with our results, Calero et al (2021) reported that patients who had undergone ICBT with and without guidance sessions showed a statistically significant improvement in automatic thoughts measure [ 68 ]. Similar to our results, previous studies have reported no significant differences between ICBT and CBT in the improvement of automatic thoughts of subjects [ 33 , 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was found that the ICBT achieved comparable scores on the improvement of cognitive therapy awareness compared with the CBT treatment. In line with our results, Calero et al (2021) reported that patients who had undergone ICBT with and without guidance sessions showed a statistically significant improvement in automatic thoughts measure [ 68 ]. Similar to our results, previous studies have reported no significant differences between ICBT and CBT in the improvement of automatic thoughts of subjects [ 33 , 67 ].…”
Section: Discussionsupporting
confidence: 92%